Design Of Home-Based Heart Monitoring System Using Electrocardiogram (ECG) - Gunaratnam, Thamendaran; Ramli, Nur Ilyani (Evolution in Electrical and Electronic Engineering, 2023)
The rapid development of technology in the current era has been very important in achieving balance in a healthy lifestyle. With the constant evolution of technological development, the possibilities of having advanced, affordable, and accessible medical devices are easier than usual. This development provides challenges and opportunities for healthcare providers to manage patients remotely. In this project, a heart rate monitoring system using a Nodemcu microcontroller and an AD8232 sensor is developed and connected to the IoT platform of Ubidots. The AD8232 sensor is used to detect the electrical activity of the heart and convert it into a readable analog signal. The Nodemcu is then used to read this signal and send it to the Ubidots IoT platform, where the data can be visualized and analyzed in real time. The system allows for remote monitoring of heart rate and can be useful in various applications such as monitoring the health of patients with cardiac conditions. The aim is to create a system for monitoring the heart signal and activities to identify how healthy the heart is. The project is done by testing volunteers who have different health rates and tested with the activities done before taking the reading on the ECG. The results visualize the ECG reading of the subject to the IoT platform and the condition of the heart can be interpreted by specialists.